Mapping the Landscape of Experiential Education - Meyer, Joshua (Experiential Learning and Teaching in Higher Education, 2025)
This concept paper proposes a way of mapping instructional landscapes to improve the practice of experiential programming. It begins by reviewing how experiential education has been defined including requests from that literature base for better definitional clarity. It then reviews a recent initiative commissioned by the Society for Experiential Education to update its institutional definition. Heinrich and Green’s (2025) prototypes, which are the products of that process, are presented and discussed. This article then examines a recently published definitional model (Meyer, 2024), compares that model to Heinrich and Green’s prototypes, and applies Meyer’s model to analyze two, hypothetical, high-impact teaching practice scenarios with the goal of mapping the definitional features of each scenario. This approach provides direction for validating a framework of definitional features, and it also enables Meyer’s model to be critically examined. Thus, this paper addresses Heinrich and Green’s (2025) call to action as it offers a conceptual and pedagogical entry point into experiential education (Prototype 1) that also provides useful insight for institutional stakeholders (Prototype 2).